2019
DOI: 10.1186/s13229-018-0246-0
|View full text |Cite
|
Sign up to set email alerts
|

Autism prevalence in China is comparable to Western prevalence

Abstract: Background Autism prevalence in the West is approximately 1% of school age children. Autism prevalence in China has been reported to be lower than in the West. This is likely due to at least two reasons: (1) most studies in China only included the special school population, overlooking the mainstream school population; and (2) most studies in China have not used contemporary screening and diagnostic methods. To address this, we tested total autism prevalence (mainstream and special schools) in Jil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
131
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(140 citation statements)
references
References 26 publications
6
131
1
2
Order By: Relevance
“…Autism spectrum disorder (ASD) is a neurodevelopmental disorder with an increasing global prevalence ranging from 42.6/10,000 in China to 1/58 in the United States 1,2 . ASD can be reliably diagnosed at 24 months or even as early as 18 months of age 3 , and is a life-long condition.…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is a neurodevelopmental disorder with an increasing global prevalence ranging from 42.6/10,000 in China to 1/58 in the United States 1,2 . ASD can be reliably diagnosed at 24 months or even as early as 18 months of age 3 , and is a life-long condition.…”
Section: Introductionmentioning
confidence: 99%
“…3 Singapore Institute for Clinical Sciences (SICS), Agency for Science, Technology and Research (A*STAR), Singapore, Singapore. 4 Department of Paediatrics, Yong Loo Lin School of Medicine, National University of Singapore, Singapore, Singapore. 5 Khoo Teck Puat-National University Children's Medical Institute, National University Health System, Singapore, Singapore.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) refers to a developmental and neurobehavioral condition characterized by deficits in social communication and social interaction across multiple contexts with restricted, repetitive patterns of behaviour, interests, or activities [1]. Recent data suggest that as many as 1 in 59 children are diagnosed with ASD, although other reports not using parental report and school age children generally show a prevalence of 1% globally, with little regional variations in developed countries within North America, Western Europe, Central Latin America, and Asia Pacific [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates are that ASD affects 1/59 children aged 8 years old (Baio et al, 2018), which is higher than the prevalence of 1/68 children in 2012 (Christensen et al, 2016) and the estimates of 1/110 children in (Autism and Developmental Disabilities Monitoring Network Surveillance Year 2006Principal Investigators, 2009. A recent search for the prevalence of ASD in China found that Jilin City has a similar prevalence of autism in China to that in the West, at approximately 1%, and the results from Shenzhen and Jiamusi cities are also in line with Western estimates (Sun et al, 2019). Sensory processing differences have long been associated with ASD, and they have recently been added to the diagnostic criteria for the updated diagnostic criteria in the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-V) (American Psychiatric Association, 2013).…”
Section: Introductionmentioning
confidence: 70%